158k views
5 votes
Given f(x) = 3x − 10 and g(x) = 12x + 8, solve for (f + g)(x) and select the correct answer below. (f + g)(x) = 15x − 2 (f + g)(x) = 9x − 2 (f + g)(x) = 15x + 2 (f + g)(x) = 36x2 − 120x

User McKayla
by
5.7k points

2 Answers

1 vote
(f+g)(x) simple means adding both f(x) and g(x). This means that

(f+g)(x) = 3x-10 + (12x + 8)
= 15x-2
User Ricardo Gaefke
by
5.0k points
3 votes

Answer: First option is correct.

Explanation:

Since we have given that


(x) = 3x-10\\\\g(x) = 12x + 8

We need to find the addition of two functions i.e. f and g.

So, it becomes,


(f+g)(x)=3x-10+12x+8\\\\(f+g)(x)=15x-2

Hence, the addition of two functions is (f+g)(x)=15x-2.

Therefore, first option is correct.

User Mateva
by
5.0k points